ExoIII and TdT dependent isothermal amplification (ETDA) colorimetric biosensor for ultra-sensitive detection of Hg2+. (30th June 2020) - Li, XiangYang; Du, ZaiHui; Lin, Shenghao; Tian, JingJing; Tian, HongTao; Xu, WenTao
Highlights: A colorimetric biosensor was constructed for ultra-sensitive detection of Hg 2+ The activity of Exo IIIwas activated by T-Hg 2+ -T mismatch The background value was reduced by inhibiting of TdT activity with -NH2 The TdT was activited for the formation of G-rich nucleic acid sequences The cyclic amplification reaction release Hg 2+ to next round of specific recognition Abstract: As the accumulation of mercury ions has a detrimental impact on human health, the design and development of a new type of biosensor that can rapidly, sensitively and selectively detect Hg 2+ in aqueous solutions are essential. In this study, we have developed an exonuclease III ( Exo III) and Terminal deoxynucleotidyl transferase (TdT) dependent isothermal amplification (ETDA) colorimetric biosensor. The template sequence is a hairpin where -NH2 is labeled at the 3′-end and both termini are T -rich sequences. In the presence of Hg 2+, the template formed a blunt end, and the catalytic activity of Exo III was activated with cleavage of the -NH2 at the 3′-end. TdT enzyme activity was initiated with the formation of a large number of G-rich nucleic acid sequences. G-rich sequences incubated with iron (III)-hemin mimicked peroxidase-like activity, catalyzing the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of H2 O2 . The biosensor constructed in this paper had a good linear range, 1–25 nmol/L. Its detection limit was 0.41 nmol/L (3σ), and recovery rates were between 100.5% and 103%. In conclusion, combined with the colorimetric biosensor and double enzyme cyclic amplification reaction, an ultra-sensitivity and strong specificity detection method was developed to detect Hg 2+ . At the same time, this method also expands the detection method of Hg 2+ available in the literature.